The construction of the Occupational Therapy practice in the Medical Clinic of a Teaching Hospital of the Municipality of Belém, Pará, Brazil (Research, Society and Development, 2021)
This paper presents a descriptive and cross-sectional experience report of a supervised internship experienced by students in the last year of the Occupational Therapy course under teaching supervision in the medical clinic sector of a teaching hospital in the metropolitan region of Belém. The Model was used as a reference. of Human Occupation (MOHO) for the development of professional practice, with interventions aimed at training in Activities of Daily Living (ADL), psycho-emotional skills, cognitive stimulation, in addition to prescription and training in Assistive Technology (AT), routine organization. With the interventions, it was possible to observe in the patients greater engagement and improvement in the performance of their activities in the in-hospital context, becoming more active and active in the health-disease process. As for the perspective of the students about their performance in the sector, the importance of learning and clinical reasoning in the face of the demands presented by the assisted patients and by the flow of the hospital service is highlighted.